STUDI TENTANG IMPLEMENTASI NILAI – NILAI TABIAT LUHUR DI PONDOK PESANTREN PELAJAR DAN MAHASISWA MIFTAHUL HUDA KOTA PEKANBARU - Muhammad Maftuh Al Faqih; Zahirman Zahirman; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the implementation of noble character values honest, trustworthy, hard work, thrifty, harmonious, trustworthy, and cooperation Good students of the Pondok Pesantren Pelajar dan Mahasiswa Miftahul Huda, Pekanbaru. In data processing the researcher uses quantitative data analysis. The sample of this study was 51 students of Pondok Pesantren Pelajar dan Mahasiswa Miftahul Huda Pekanbaru City, consisting of 4 students and 47 students. The data retrieval technique used by researchers is to use questionnaires / questionnaires to students, interviews with teacher boards, and observation or seeing directly to the field. The author formulates research problems, namely „'How are the implementation of noble character values carried out at the Pondok Pesantren Pelajar dan Mahasiswa Miftahul Huda?'. The benefit for board administrators is to be able to map and design the implementation of noble character values so that it can run optimally, it is expected to be a material for evaluation and stabilization in the character building of the students. After doing the research, it can be concluded that the implementation of noble character values has gone well, but the need for development in applying them. The results of data processing show that the percentage of respondents' answers as a whole is quite good as much as 54.21% which is located in rank 50% - 75%. Based on the results of the study, it can be concluded that the study of the implementation of noble behavioral values at the Pondok Pesantren Pelajar dan Mahasiswa Miftahul Huda Pekanbaru City was carried out reasonably well.Key Words: Implementation, Noble Character Values